Embryo vitrification impacts learning and spatial memory by altering the imprinting genes expression level in the mouse offspring’ hippocampus - Samira Hosseini; Sara Hosseini; Hadi Aligholi; Mohammad Salehi (Scientific Reports, 2025)
Abstract The safety and impact of embryo vitrification as a more reliable approach for cryopreservation in assisted reproductive techniques (ARTs) on the nervous system is uncertain. This study was aimed to investigate the expression level of imprinting genes in the hippocampus of offspring derived from vitrified embryo transfer. The hippocampus of the 2-day-old offspring from three experimental groups included vitrification (blastocysts derived from vitrified embryos), sham (the embryos at the blastocyst stage obtained through in vitro fertilization (IVF)) and control was removed for molecular, histological and behavioral analysis. There was no statistically noteworthy difference in survival, cleavage and blastocysts rate between vitrification and sham groups. Dnmt1, Dnmt3a, 3b and Igf2 upregulated in the vitrified group compared to the sham and control groups. The gene expression level of Meg3 declined dramatically and the intensity of DNA methylation in CpG island of Meg3 significantly elevated in the vitrification group. A notable disparity was observed in the quantity of dark neurons in the hippocampus of the offspring, spatial learning and memory abilities between the control and vitrification groups. According to these results, embryo vitrification may alters gene expression in brain hippocampus tissue and disturbs genomic imprinting, dark neuron formation and spatial memory.